+0  
 
0
343
1
avatar
2^n=radical(3^(n-2))
Guest Feb 10, 2012
 #1
avatar+3077 
0
2^n=sqrt(3^(n-2))

:: if nothing else seems to work, try 'ln( )' on both sides:
ln( 2^n ) = ln( sqrt(3^(n-2)) )
:: logarithm law: ln( x^y ) => y*ln(x) (x,y >0)
:: sqrt( x ) = x^(1/2)
n*ln(2) = ln( (3^(n-2))^(1/2) )
:: pow law
n*ln(2) = ln( (3^(1/2*(n-2))) )
n*ln(2) = 1/2*(n-2)*ln( 3 )
n*ln(2) = 1/2*n*ln( 3 ) - ln( 3 )
n*ln(2) - 1/2*n*ln( 3 ) = -ln( 3 )
n*( ln(2) - 1/2*ln(3) ) = -ln( 3 )
n = -ln( 3 ) / ( ln(2) - 1/2*ln(3) )
n = -2*ln( 3 ) / ( 2*ln(2) - ln(3) )
admin  Feb 11, 2012

45 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.